DAMPAK SISTEM ZONASI TERHADAP MUTU SEKOLAH - Lestari, Hana; Rahmawati, Ima; Rohimah, Siti (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2024)
The government is strongly committed to improving education standards. One strategy to improve school quality is to create a school zoning policy. The purpose of this study is to determine how the government zoning scheme affects school quality. This study uses a qualitative methodology that includes observation, literature review, and semi-structured interview techniques. As a preliminary investigation, there is only one informant in this study. By selecting certain individuals who are considered to have knowledge of the zoning system, a qualitative research design is used. The findings of the study indicate that the zoning system has no effect on the quality of most schools both before and after its implementation.